Contribution To The Role of Madrasah Management In Improving The Quality of Education - Zulkarnain, Iskandar; Handoko, Cipto; Andari, An An; Lestari, Sri (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Improving the quality of education is one of the main pillars of education development in Indonesia. Quality education will produce smart and competitive human resources (HR). This study aims to find out how the contribution of madrasah management in improving the quality of education at MA Hidayatul Mubtadiin Sidoharjo Jati Agung.. This research uses qualitative descriptive research methods. Data collection techniques in the form of observations, interviews, and documentation. Data analysis includes data collection, data presentation, and drawing conclusions. The results of the study showed that the implementation of management functions in improving the quality of learning in madrasah aliyah hidayatul mubtadiin sidoharjo, namely by: 1) Curriculum Management and Learning Programs, 2) Management of educational personnel, 3) Student management, 4) Financing / Financial Management, 5) Management of Facilities and Infrastructure, 6) Management of madrasah relations with the community.Furthermore, the supporting factors for the implementation of the Management function in Improving the Quality of Learning are: 1) The leadership of an experienced Madrasah head, 2) Teachers already have professional competence, 3) Adequate learning facilities. Meanwhile, the inhibiting factors include: 1) The number of learning hours that are lacking, 2) Students' lack of attention to learning materials that can interfere with the learning process, 3) The emergence of behaviors that interfere with the learning process, 4) Teachers do not master classroom management techniques in the learning process, there are often continuous disturbances, for example, students carry out behaviors that can interfere continuously and repeatedly.